Derecho Ambiental Ecuatoriano, quo vadis? - Mónica Ribadeneira Sarmiento (Universidad Hemisferios, 2016)
Environmental Law, recognized as such, is one of the most modern branches of law and the study of its history and evolution divides the authors. Based on a historical review, the article presents the concept and principles of environmental law and concludes with an analysis of the constitutional texts; it proves that those principles (consequence of the referred historical review) are weakened. The article includes in its conclusions a warning about the consequences of this gradual weakening. The main objective of this article is to present the evolution of environmental law to contribute their disclosure and evidence that the importance of art in its definition to avoid weakening. This paper was written using documentary sources, literature review of research and articles by renowned writers. It contains: (i) introduction, (ii) Global and Latin American historical development, (iii) concept and principles of environmental law, (iv) brief analysis of environmental norms in the Constitution of Ecuador, emphasizing those relating to the Rights of Nature and the case of the genetically modified organisms, and concludes exposing on the prospect of future development of environmental law in Ecuador.